IMPLEMENTATION COBIT 2019 FOR EVALUATION OF HEALTH CLINIC INFORMATION SYSTEM GOVERNANCE IN CENTRAL JAVA - Ilham Akbar Sodik; Dinar Mutiara Kusumo Nugraheni (Jurnal Teknik Informatika (Jutif), 2022)
The clinic is one of the small and medium-scale public facilities that provide individual health services with basic and detailed services. The application of information systems in health clinics has been carried out in recent years to support good performance in health services for the community. This study aims to evaluate the capability of information system governance that has been implemented in health clinics. The evaluation of this information system uses COBIT 2019. The latest framework is used as a guide in the evaluation of governance. COBIT 2019 has 10 design factors and 40 domains, which will then be the top domains that will be used to analyze information system capabilities. The results were obtained in several domains, including BAI02, BAI03, and BAI07. Furthermore, the results were obtained from the level of information system capability for each domain, namely the BAI02 domain with level 3 capability, the BAI03 domain with level 4 capability, and the BAI07 domain with level 3 capability. Two domains still have gaps, namely BAI02 and BAI07. Then this research also produces several recommendations to achieve the specified target level, such as being able to build your information system without relying on third parties and being able to design operational standards and guidelines that can be used in the transition to technological change.